The impact of project-based learning on integrated school well-being on fifth-grade students’ natural and social sciences outcomes - Priandita Mindiari; Roemintoyo Roemintoyo; Mintasih Indriayu (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2026)
Elementary science education in Indonesia often remains teacher centered and offers limited opportunities for active inquiry, necessitating innovative strategies to boost both learning outcomes and student well being. This study investigated the effect of Project-Based Learning (PjBL) integrated with School Wel -Being on fifth grade students’ Natural and Social Sciences (IPAS) achievement under the Kurikulum Merdeka. A quasi-experimental pretest–posttest control group design involved an experimental class receiving PjBL enriched with the four well-being dimensions (having, loving, being, health) and a control class using standard PjBL. This study involved 48 students from to elementary schools. Data were collected through a validated IPAS achievement test and observation checklist, then analyzed using Shapiro Wilk and Levene tests for normality and homogeneity, independent-samples t-test for group comparisons, and N-Gain. Results showed the experimental group achieved a higher mean posttest score, a larger mean N-Gain (0.58 vs. 0.38), and consistently strong implementation of the loving and being dimensions.  School Well-being as reinforcement in each step of PJBL to strengthen the results of natural and social sciences learning. The result of this study indicated that the selection of the right learning model that is reinforced using School Well-being can significantly improve  natural and social sciences outcomes in Elementary School.